Acquired reactive perforating collagenosis: A report of a typical case. Issue 30 (July 2016) - Fei, Chengwen; Wang, Yao; Gong, Yu; Xu, Hui; Yu, Qian; Shi, Yuling
Abstract: Background: Reactive perforating collagenosis (RPC) is a rare form of transepithelial elimination, in which altered collagen is extruded through the epidermis. There are 2 types of RPC, acquired RPC (ARPC) and inherited RPC, while the latter is extremely rare. Here we report on 1 case of ARPC. Methods: A 73-year-old female was presented with strongly itchy papules over her back and lower limbs for 3 months. She denied the history of oozing or vesiculation. A cutaneous examination showed diffusely distributed multiple well-defined keratotic papules, 4 to 10 mm in diameter, on the bilateral lower limbs and back as well as a few papules on her chest and forearm. Scratching scars were over the resolved lesions while Koebner phenomenon was negative. The patient had a history of type 2 diabetes for 15 years. Laboratory examinations showed elevated blood glucose level. Skin lesion biopsy showed a well-circumscribed area of necrosis filled with a keratotic plug. Parakeratotic cells and lymphocytic infiltration could be seen in the necrosed area. In dermis, sparse fiber bundles were seen perforating the epidermis. These degenerated fiber bundles were notarized as collagen fiber by elastic fiber stain, suggesting a diagnosis of RPC. Results: Then a diagnosis of ARPC was made according to the onset age and the history of diabetes mellitus. She was treated with topical application of corticosteroids twice a day and oral antihistamine once a day along with compound glycyrrhizin tablets 3 times a day. And the blood glucose was controlled in a satisfying range. Two months later, a significant improvement was seen in this patient. Conclusion: Since there is no efficient therapy to RPC, moreover, ARPC is considered to be associated with some systemic diseases, the management of the coexisting disease is quite crucial. The patient in this case received a substantial improvement due to the control of blood glucose and application of compound glycyrrhizin tablets.